Characteristics of Older Individuals with Asthma Being Treated with Biologics - Aetou M; Kiskinov Y; Ratsimba SFN; Barth M; Pizarro C; Bergs I; Spiesshoefer J; Skowasch D; Dreher M (Journal of Asthma and Allergy)
Maria Aetou,1,* Yavor Kiskinov,2,* Sitraka Faniry Nantenaina Ratsimba,1 Maximilian Barth,1 Carmen Pizarro,2 Ingmar Bergs,1 Jens Spiesshoefer,1 Dirk Skowasch,2,* Michael Dreher1,* 1Department of Pneumology and Intensive Care Medicine, University Hospital RWTH Aachen, Aachen, Germany; 2Department of Internal Medicine II, Cardiology, Pneumology and Angiology, University Hospital Bonn, Bonn, Germany*These authors contributed equally to this workCorrespondence: Maria Aetou, Department of Pneumology and Intensive Care Medicine, University Hospital RWTH Aachen, Pauwelsstrasse 30, Aachen, Germany, 52074, Tel +0049 2418088763, Email maetou@ukaachen.dePurpose: Biologic (antibody) therapy is a safe, effective, and guideline-recommended treatment for patients with severe and otherwise uncontrolled asthma. The number of older individuals with asthma is increasing but there is a lack of data on the use of biologics in this cohort. Therefore, this study reports the characteristics of older individuals receiving biologic therapy for severe asthma.Patients and Methods: This study was a retrospective data analysis conducted at two centers in Germany.Results: Eighty-eight patients were included (52 aged 50– 59 years and 36 aged ≥ 60 years). There was a high rate of comorbidities and associated pharmacological therapy use. Nearly half (49%) of participants were current or ex-smokers and 29% had chronic obstructive pulmonary disease. The older age group (≥ 60 years) had significantly more cardiovascular comorbidities, more comorbidities overall, and a worse diffusion capacity compared with the group aged 50– 59 years. Baseline lung function parameters, and the change in lung function after 6 months of biologic therapy, did not differ significantly between the two age groups. Participants aged ≥ 60 years used self-injection less than those aged 50– 59 years.Conclusion: These data help to characterize the specific population of older people receiving biologic therapy for severe asthma, and showed a high rate of comorbidities, polypharmacy, and poor diffusion capacity in this group.Keywords: antibodies, asthma, biologics, elderly, lung function